Recommended Effective Throat Sizes for Flare Groove Welds to HSS - Packer, Jeffrey A.; Frater, George S. (Engineering Journal, 2005)
An experimental research project has been undertaken to investigate the geometric properties, and in particular the effective throat size, of flare bevel and flare-V partial joint penetration groove welds at the corners of Hollow Structural Sections (HSS). HSS-to-plate (flare bevel) and HSS-to-HSS (flare-V) single-pass welds were carefully performed to Welding Procedure Specifications agreed within a Project Oversight Committee, using ASTM A500 tubing, then cross-sectioned after inspection to produce 180 test welds. Parameters included three HSS sizes (with wall thicknesses ranging from 3/16 in. to 3/8 in.), four welding processes (FCAW-G, FCAW-S, GMAW and SMAW) and four welding positions (flat, horizontal, vertical and overhead). All weld cross-sections were polished and etched, then had their profiles digitally recorded and measured. An analysis of the resulting data has shown that the current pre-qualified effective throat sizes for these two weld types, in AWS D1.1/D1.1M:2004, can be made more liberal for most weld processes.